The Effect of Online Sales and Consumer Trust on Interest in Buying Clothing Products at E-Commerce Shopee - Adhelia Shinta Balqis; Hepiana Patmarina (International Journal of Economics, Business and Innovation Research, 2024)
This study aims to examine the effect of online sales as well as consumer confidence on buying interest in clothing products in Shopee e-commerce. This research method uses a quantitative approach by distributing questionnaires to respondents who are active Shopee users. The data were analyzed using multiple linear regression techniques to test the relationship between the variables of online sales, consumer confidence, and purchase intention of clothing products. The results of the analysis show that online sales have a significant positive effect on buying interest in clothing products at Shopee. In addition, consumer trust also has a significant positive effect on purchase intention of clothing products on the platform. These results show the importance of an effective online sales strategy and building consumer trust in increasing consumer buying interest in clothing products in Shopee e-commerce.